2018
DOI: 10.17957/ijab/15.0495
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa Response to Lead: Growth and Lead Partitioning

Abstract: Chenopods are known for salt and metal ion tolerance. Chenopodium quinoa is a recent introduction in the country but yet to be tested on metal contaminated soils. A pot experiment was conducted to explore growth and phytoextraction potential of four quinoa lines (A1, A2, A7 and A9) against different lead concentrations (0, 50 and 100 mg kg -1 ). Required lead concentrations were developed in polythene bags filled with sandy loam soil (5 kg) using lead nitrate salt prior to two month sowing and kept sealed up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…The use of the plant, e.g., quinoa as phytoextraction, is an exciting approach nowadays [24][25][26]. The present study indicated that four quinoa lines showed differential responses regarding Ni accumulation.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The use of the plant, e.g., quinoa as phytoextraction, is an exciting approach nowadays [24][25][26]. The present study indicated that four quinoa lines showed differential responses regarding Ni accumulation.…”
Section: Discussionmentioning
confidence: 52%
“…A high concentration of heavy metal, e.g., Pb, reduced the growth and PLOS ONE photosynthetic pigment. Lead concentration adversely affects the chloroplast structure, which results in reduced enzyme activity, reduced CO 2 fixation, and photosynthetic efficiency [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that Cd had the highest bioconcentration factor (31), followed by Fe (30), Cu (19), Ni (5), Zn (3), and Cr (2) [52,98]. Haseeb et al [103] undertook a study on four quinoa lines and observed that they have significant phytoextractive and hyper-accumulative potential. Interestingly, while the presence of Pb in different plant components inhibits some physiological function and yields, they alluded that the amount in the seeds is within the recommended safe limit [104] and, therefore, it does not pose a threat to human health.…”
Section: Phytoremediationmentioning
confidence: 99%